The Mph1 Helicase can promote telomere uncapping and premature senescence in budding yeast - Luke-Glaser, Sarah; Luke, Brian (PLOS ONE, 2012)
Double strand breaks (DSBs) can be repaired via either Non-Homologous End Joining (NHEJ) or Homology directed Repair (HR). Telomeres, which resemble DSBs, are refractory to repair events in order to prevent chromosome end fusions and genomic instability. In some rare instances telomeres engage in Break-Induced Replication (BIR), a type of HR, in order to maintain telomere length in the absence of the enzyme telomerase. Here we have investigated how the yeast helicase, Mph1, affects DNA repair at both DSBs and telomeres. We have found that overexpressed Mph1 strongly inhibits BIR at internal DSBs however allows it to proceed at telomeres. Furthermore, while overexpressed Mph1 potently inhibits NHEJ at telomeres it has no effect on NHEJ at DSBs within the chromosome. At telomeres Mph1 is able to promote telomere uncapping and the accumulation of ssDNA, which results in premature senescence in the absence of telomerase. We propose that Mph1 is able to direct repair towards HR (thereby inhibiting NHEJ) at telomeres by remodeling them into a nuclease-sensitive structure, which promotes the accumulation of a recombinogenic ssDNA intermediate. We thus put forward that Mph1 is a double-edge sword at the telomere, it prevents NHEJ, but promotes senescence in cells with dysfunctional telomeres by increasing the levels of ssDNA.